Simulation and Modeling CUK H-Bridge Current-Controlled Inverter Using a Proportional-Integral Algorithm - Fahrul Indra; Eka Nuryanto Budisusila (Emitor: Jurnal Teknik Elektro, 2026)
The growing demand for renewable energy drives the need for efficient and reliable power conversion systems. This paper presents the simulation and modeling of a CUK H-Bridge Inverter with current control using a Proportional Integral (PI) algorithm implemented in Power Simulator (PSIM) software. The proposed topology combines an H-Bridge inverter with a CUK AC–AC converter, enabling bidirectional power flow, buck-boost voltage operation, and low Total Harmonic Distortion (THD) in the output current. The current control loop uses a PI controller tuned using the empirical Ziegler–Nichols (Z-N) method, followed by fine-tuning, resulting in optimal parameters of Kp = 0.6, Ti = 0.0167, and Ki = 35. Simulation results show that the actual output current (Iact) accurately follows the reference current (Iref) with minimal steady-state error. The topology operates in buck mode (Vo < Vin), steady-state mode (Vo ≈ Vin), and boost mode (Vo > Vin) depending on the given reference current value. A maximum output power of 2.25 kW is achieved at a reference current of 15 A with a maximum output voltage of 150 V. The measured output current THD is 3.6%, meeting the IEEE 519 standard. These results confirm the effectiveness of the PI-controlled CUK H-Bridge Inverter topology for renewable energy applications.